Monitoring the effectiveness of root canal procedures on endotoxin levels found in teeth with chronic apical periodontitis - Ariane Cassia Salustiano MARINHO; Frederico Canato MARTINHO; Alexandre Augusto ZAIA; Caio Cezar Randi FERRAZ; Brenda Paula Figueiredo de Almeida GOMES (University of São Paulo, 2014)
Objective: The aim of this study was to monitor the effectiveness of root canal procedures by using different irrigants and intracanal medication on endotoxin levels found in root canals of teeth with chronic apical periodontitis. Material and Methods: Thirty root canals of teeth with pulpal necrosis associated with periapical lesions were selected and randomly divided into groups according to the irrigants used: GI - 2.5% NaOCl, GII - 2% chlorhexidine (CHX) gel, and GIII - saline solution (SS) (all, n=10). Samples were collected with sterile/apyrogenic paper points before (S1) and after root canal instrumentation (S2), after use of 17% ethylenediaminetetraacetic acid (EDTA) (S3), and after 30 days of intracanal medication (Ca(OH)2+SS) (S4). A turbidimetric kinetic Limulus Amebocyte Lysate assay was used for endotoxin measurement. Results: Endotoxins were detected in 100% of the root canals investigated (30/30), with a median value of 18.70 EU/mL. After S2, significant median percentage reduction was observed in all groups, irrespective of the irrigant tested: 2.5% NaOCl (99.65%) (GI), 2% CHX (94.27%) (GII), and SS (96.79%) (GIII) (all p<0.05). Root canal rinse with 17% EDTA (S3) for a 3-minute period failed to decrease endotoxin levels in GI and a slight decrease was observed in GII (59%) and GIII (61.1%) (all p>0.05). Intracanal medication for 30 days was able to significantly reduce residual endotoxins: 2.5% NaOCl (90%) (GI), 2% CHX (88.8%) (GII), and SS (85.7%) (GIII, p<0.05). No differences were found in the endotoxin reduction when comparing s2 and s4 treatment groups. Conclusion: Our findings demonstrated the effectiveness of the mechanical action of the instruments along with the flow and backflow of irrigant enduring root canal instrumentation for the endotoxin removal from root canals of teeth with chronic apical periodontitis. Moreover, the use of intracanal medication for 30 days contributed for an improvement of endotoxin reduction.